The influence of different implements on kinematics and kinetics compared to men`s javelin throw - Köhler, H.-P.; Witt, M. (Journal of Applied Biomechanics, 2025)
Javelin throwers cannot safely throw with a long approach run often per training session. Therefore, implements of different shapes and masses are thrown from short run-ups to emulate the demands of achieving high throwing distances. This study examined the effects of different implements, thrown from various approaches, on the kinematics and kinetics of the throwing arm. The throwing motions of 6 athletes, each throwing 6 different implements were recorded using 12 infrared cameras. Kinematics and kinetics of the shoulder and elbow joints were calculated and statistically compared. The results show that lighter implement throws achieved higher release speeds, while heavier implements required greater work to be done on them. We identified significant differences for the shoulder external rotation angle (P < .001), the shoulder internal rotation (P = .040), and elbow extension (P = .003) angular velocities and the torques of the shoulder internal rotation (P = .006), horizontal flexion (P = .004), and the elbow varus (P = .008). It can be concluded that throws with balls of different masses have different angular velocities and joint torques, and therefore can be used to train speed and strength aspects of the javelin throw while using lower run-up speeds.